2021
DOI: 10.1002/mawe.202000089
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the corrosion behavior of aluminum bronze alloy in alkaline environment

Abstract: In this study, the effect of amino‐based additives including ammonia, ethanolamine and a mixture of two additives on the pH change of condenser water and corrosion behavior of aluminum bronze alloy as a structural material of condenser were investigated. The results of polarization curves, wheel tests and inductively coupled plasma showed that by increasing the pH from 8.5 to 10.5, the corrosion rate of aluminum bronze alloy and the dissolution rate of alloying elements are increased. The effect of amino‐based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…3a, but active behavior is observed in ammonia systems, implying that anodic active dissolution occurs. This demonstrates that the concentration of ammonia used for this work is appropriate, in contrast to the passivation behavior caused by low concentrations that has been discussed in the literature [38,39]. The corrosion current density (i corr ), polarization resistance (R p ), corrosion rate (CR), and anodic/cathodic Tafel slopes (β and β c , respectively) are calculated and listed in Table S1.…”
Section: Corrosion Behavior Of H62 Brassmentioning
confidence: 88%
“…3a, but active behavior is observed in ammonia systems, implying that anodic active dissolution occurs. This demonstrates that the concentration of ammonia used for this work is appropriate, in contrast to the passivation behavior caused by low concentrations that has been discussed in the literature [38,39]. The corrosion current density (i corr ), polarization resistance (R p ), corrosion rate (CR), and anodic/cathodic Tafel slopes (β and β c , respectively) are calculated and listed in Table S1.…”
Section: Corrosion Behavior Of H62 Brassmentioning
confidence: 88%
“…Electrolytes are also a decisive factor influencing the corrosion of NAB alloys. For instance, sulfide-polluted corrosive medium, 114 increased temperature, 86 higher pH of alkaline media, 115 and time-dependent magnetic fields 116 have been reported to adversely affect the corrosion resistance of NAB alloys. However, the impact of flow rate on corrosion rate remains uncertain, 86,113 as it depends on the solution type and its properties.…”
Section: Discussionmentioning
confidence: 99%
“…The corrosion characteristics of NAB were assessed in various alkaline solutions of ammonia, ethanolamine, and a mixture of ammonia + ethanolamine in different ratios. 115 It was observed that an increase in pH value had an adverse impact on the corrosion performance of the alloy. Specifically, pH values exceeding 10 resulted in a significant increase in corrosion rate, mainly due to the higher solubility of the alumina film under such experimental conditions.…”
Section: Corrosion Behavior Of Conventional Nab Alloysmentioning
confidence: 99%
See 1 more Smart Citation